Low energy ion irradiation studies of fullerene C70 thin films – An emphasis on mapping the local structure modifications. (June 2018) - Singhal, Rahul; Bhardwaj, Jyotsna; Vishnoi, Ritu; Aggarwal, S.; Sharma, Ganesh D.; Pivin, J.C.
Abstract: Metal matrix composites have a diverse range of applications. We have probed local structural modifications taking fullerene C70 as a model matrix material. In this study, thin films of fullerene C70 were grown on polished silicon and quartz substrates by resistive heating of fullerene C70 . In order to understand local structural changes, these semi-crystalline films were irradiated with 120 keV N + ions at different fluences ranging from 1 × 10 13 to 3 × 10 16 ions.cm −2 . Microscopic analysis shows an increase in topological roughness up to a fluence of 1 × 10 15 ions.cm −2 and then a decrease. The size of the particles decreases with increase in the fluence. Various spectroscopic analyses conducted on differently irradiated fullerene C70 films show that the bandgap decreases with the increase in the fluence which will increase the conductivity of the irradiated thin films. These results are proved by I-V measurements showing the decrease in the resistivity at higher fluences. Therefore, this characteristic trait makes fullerene C70 to be used as a prominent matrix component in the composites. Raman spectroscopic investigations reveal that C70 is completely transformed into amorphous carbon at a fluence of 3 × 10 16 ions.cm −2 . Different vibrational modes in FT-IR are also reported in the present work. Highlights: C70 Fullerene thin films were irradiated by 120 keV N + ions. The optical and morphological changes were observed. Semi crystalline thin film converted into amorphous Carbon. Band gap decreases and conductivity increases with the increase in fluence.